2022
DOI: 10.1111/1365-2664.14232
|View full text |Cite
|
Sign up to set email alerts
|

Tree species that ‘live slow, die older’ enhance tropical peat swamp restoration: Evidence from a systematic review

Abstract: Degraded tropical peatlands lack tree cover and are often subject to seasonal flooding and repeated burning. These harsh environments for tree seedlings to survive and grow are therefore challenging to revegetate. Knowledge on species performance from previous plantings represents an important evidence base to help guide future tropical peat swamp forest (TPSF) restoration efforts. We conducted a systematic review of the survival and growth of tree species planted in degraded peatlands across Southeast Asia to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 72 publications
0
24
1
Order By: Relevance
“…Marginal R 2 , conditional R 2 and intra-class correlations (ICC) showing variation explained by fixed and random effects terms. studies showed no significant effect of prior drainage on seedling mortality, but found species choices to be important-slower growing tree species survived for longer [47].…”
Section: Discussion (A) Demographic Fate Of Planted Treesmentioning
confidence: 96%
See 3 more Smart Citations
“…Marginal R 2 , conditional R 2 and intra-class correlations (ICC) showing variation explained by fixed and random effects terms. studies showed no significant effect of prior drainage on seedling mortality, but found species choices to be important-slower growing tree species survived for longer [47].…”
Section: Discussion (A) Demographic Fate Of Planted Treesmentioning
confidence: 96%
“…Our datasets were compiled from online literature searches following the protocols outlined below (see electronic supplementary material, appendix S1 for further details), supplemented by additional published studies compiled by co-authors S.W.S. and N.E.B.R from peat swamp forest sites [47], and unpublished data and royalsocietypublishing.org/journal/rstb Phil. Trans.…”
Section: Methods (A) Data Compilationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycorrhizal inoculations can thus be incorporated with plantings to facilitate establishment, growth and canopy closure [ 89 , 90 ], with outcomes depending upon plant functional type, restoration context and time [ 91 ]. However, the role of belowground diversity can be complex, and data are lacking to identify levels of degradation that would necessitate the use of soil treatments [ 92 , 93 ]. There is also still substantial uncertainty and inter-site variability in soil carbon accumulation rates under forest recovery [ 94 ].…”
Section: Essential Science Advancesmentioning
confidence: 99%